Ammonium and Urea Transporter Inventory of the Selaginella and Physcomitrella Genomes - De Michele, Roberto; Loqué, Dominique; Lalonde, Sylvie; Frommer, Wolf B. (Frontiers in Plant Science, 2012)
Ammonium and urea are important nitrogen sources for autotrophic organisms. Plant genomes encode several families of specific transporters for these molecules, plus other uptake mechanisms such as aquaporins and ABC transporters. Selaginella and Physcomitrella are representatives of lycophytes and bryophytes, respectively, and the recent completion of their genome sequences provided us with an opportunity for comparative genome studies, with special emphasis on the adaptive processes that accompanied the conquest of dry land and the evolution of a vascular system. Our phylogenetic analysis revealed that the number of genes encoding urea transporters underwent a progressive reduction during evolution, eventually down to a single copy in vascular plants. Conversely, no clear evolutionary pattern was found for ammonium transporters, and their number and distribution in families varies between species. In particular Selaginella, similar to rice, favors the AMT2/MEP family of ammonium transporters over the plant-specific AMT1 type. In comparison, Physcomitrella presents several members belonging to both families.